1998
DOI: 10.1071/r98030
|View full text |Cite
|
Sign up to set email alerts
|

Increased chromosome abnormalities in human preimplantation embryos after in-vitro fertilization in patients with recurrent miscarriage

Abstract: Recurrent miscarriage is a pathological condition induced by maternal and embryonic causes. This paper describes a prospective study to determine the real incidence of aneuploidy for autosomes 13, 16, 18, 21, 22, and gonosomes in preimplantation human embryos obtained from patients with recurrent pregnancy loss after ovarian stimulation in an IVF-ET programme. Our results indicate that aneuploidy for the chromosomes analysed are abnormally higher in embryos obtained after IVF from recurrent abortion patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 0 publications
2
34
0
Order By: Relevance
“…No previous studies of PGD or PGS have identified an increased miscarriage rate. In fact, several studies have suggested higher ongoing pregnancy and live birth rates in women with a history of recurrent pregnancy loss (38,(51)(52)(53). Only one of the losses in the PGS group was due to an aneuploidy, trisomy 15; we did not screen for chromosome 15 as part of our PGS panel, and presumably this loss might have been averted.…”
Section: Discussionmentioning
confidence: 84%
“…No previous studies of PGD or PGS have identified an increased miscarriage rate. In fact, several studies have suggested higher ongoing pregnancy and live birth rates in women with a history of recurrent pregnancy loss (38,(51)(52)(53). Only one of the losses in the PGS group was due to an aneuploidy, trisomy 15; we did not screen for chromosome 15 as part of our PGS panel, and presumably this loss might have been averted.…”
Section: Discussionmentioning
confidence: 84%
“…Second, the prevalence of RPL among first degree relatives of women with RPL is increased approximately sixfold compared with controls (Christiansen et al 1990). Third, preimplantation genetic screening (PGS) in age matched populations shows that embryos from women with RPL have a higher incidence of aneuploidy than those from women undergoing screening for reasons not related to pregnancy loss Simó n et al 1998;Vidal et al 1998). Although only a portion of aneuploid embryos are predicted to result in a clinically detectable loss, some preimplantation genetic studies of women with RPL have detected aneuploidy in all embryos at rates approaching 50% Stern et al 1996;Daniely et al 1998;Ogasawara et al 2000;Carp et al 2001;Stephenson et al 2002;Sullivan et al 2004;Carp 2008).…”
Section: Fetal Aneuploidy In Sporadic and Recurrent Pregnancy Lossmentioning
confidence: 99%
“…Controversy exists over whether recurrent aneuploidy is a major cause of RPL (34)(35)(36)(37), because there are few age-stratified studies in the literature. In one study by Dr. Stephenson and colleagues (38), the incidence of embryonic abnormalities in miscarriages increased with age in both sporadic and recurrent pregnancy loss patients.…”
mentioning
confidence: 99%